Social networks and risk taking: Evidence from corporate control activities - LEE, Yen Teik (Institutional Knowledge at Singapore Management University, 2012)
This paper investigates the impact of social ties between the Chief Executive Officer (CEO) andboard members on corporate risk-taking in mergers and acquisitions (M&As) and on shareholdervalue. Using a measure of CEO-director connections in a large sample of U.S. firms from 2000 to2010, we document that boardroom connections lower firm acquisitiveness. If connected CEOsundertake M&As, they are less likely to choose focus acquisitions, and more likely to pay in stock.CEO-board connections do not enhance firm value in M&As. Higher levels of boardroomconnection are associated with lower announcement returns and lower subsequent return on assets.Our results are robust to alternative explanations and various robustness checks.